An Analysis of Five Contemporary Views on the Objectivity and the Validity of Religious Experiences - seyed jaber mousavi rad (حکمت اسرا)
There are many discussions about the validity and the objectivity of religious experiences among philosophers. We will analyze five main viewpoints such as Stace (the authenticity of unanimity, the ability of investigation and discipline), Swinburne (the way of credulity), Alston, John Hick (the way of similarity between perceptual and religious experiences), Rudolf Otto (the explanation of three ways for demonstration of objectivity of religious experiences) William James (the separation between experiencer and others). We say then "referring to knowledge by presence (al-'Ilm al-Huduri)" is the criteria and the proof of objectivity of religious experiences.  We can of course refer some of religious experiences to knowledge by presence and these kinds of experiences are just valid; so the experiences which are not understood by knowledge by presence like most of mystical revelations are not valid and so they can not the source of certain knowledge.